KOMUNIKASI POKDARWIS CAFE LAUT SEMARE DALAM PEMBENTUKAN CITRA DESA WISATA SEMARE KRATON PASURUAN - Muyasaroh, Siti; Rio Aushaf, Sulthan (IAI Darussalam, 2022)
This research aims to explain group communication used by tourist conscious groups in shaping the image of semare tourist village, kraton subdistrict.Semare village is a village that is known to be loud, rundown to anarchist but has various potentials in the field of marine, fisheries to tourism.Seeing this some coastal residents and teenagers around who have a high concern for the environment form a tourist conscious group.The purpose of the formation of this tourist conscious group to form the image of semare village into a tourist village.In an effort to change the image, tourist conscious groups approach by creating discussion forums and providing examples of activities to persuasion the surrounding community.As for examples of activities carried out with clean beaches, garbage collection to the provision of garbage can facilities. This research was conducted using qualitative descriptive research methods. The results of the study showed that the activities carried out had the impact of persuasion of the community.Starting from the discussion forum to all village cleaning activities. Since the formation of semare sea café now Semare Village is better known as a tourist village by the surrounding community.And provide changes to various sectors of the economy and human resources that exist.